Os diplomatas brasileiros sob a perspectiva relacional : o campo dos diplomatas e o campo político - Targa, Leandro Garcez (2017)
The thesis presents a proposal of relational analysis of the brazilian diplomats. We used the theoretical framework of Pierre Bourdieu to analyze, therefore, the agents of the field of diplomats during the period of the governments of the former presidents Fernando Henrique Cardoso (FHC) and Luiz Inácio Lula da Silva (Lula), that is, between the years of 1995 and 2010. The chosen period points to the main objective of the work: to understand the dynamics of action of diplomats based on their relationship with the process of alternation between the two governments. As a research strategy, we focus our analysis on the "game" of the field related with the process of selection and training of new diplomats. This strategy led us to the “Rio Branco Institute” (Instituto Rio Branco - IRBr), an institution linked to the Ministry of Foreign Affairs (Ministério das Relações Exteriores – MRE, also known as “Itamaraty”), which has a monopoly on the selection and training of brazilian diplomats. We assume that the diplomats are agents of the field of diplomats; therefore, they do not constitute a homogeneous group as their actions and ways of thinking the field. They are agents that share the same habitus of the field, so they are in constant dispute for the symbolic domination of the actions that lead the field. However, as a requirement of the theoretical framework, this assumption was been tested during empirical research in the same way as our initial hypothesis: the dynamics of internal disputes in the field of diplomats presents an interference from external factor, important to understand its logic of operation, which is the action of the political field. This can be observed even in an internal "game" of the field that shows high degree of autonomy like the process of selection and formation of new diplomats. We did a prosopographic study of the field agents involved in the game described. We associate this study with Geometric Data Analysis (GDA) as statistical methodology, more specifically with one of its components, Multiple Correspondence Analysis (MCA). We seek to understand the relationship between the field of diplomats and other social fields beyond the political field, such as the field of power and the field of international relations, according to the research focus. We also discussed the notion of autonomy in the field of diplomats, in addition to proposing a critical analysis of the idea "Itamaraty insulation". This work seeks to contribute to the development of the sociology of elites (or of the ruling groups) and to the still new sociology of international relations.